PERAN MATA KULIAH KEWIRAUSAHAAN DALAM MENUMBUHKAN JIWA WIRAUSAHA MAHASISWA PENDIDIKAN EKONOMI - Eriawaty; Fitriyanti (Pendidikan Ekonomi FKIP Universitas Sriwijaya, in partnership with Asosiasi Profesi Pendidikan Ekonomi Indonesia (ASPROPENDO), 2016)
Globalization today requires education to prepare the human resources (HR) quality and competitiveness. The quality of human resources is not only in the field of knowledge and skills, but also a strong mental attitude. One of the efforts made by educational institutions today is through entrepreneurship education. Introducing entrepreneurship education is expected to foster an entrepreneurial spirit among students. Entrepreneurship education in Economics education courses realized in the form of entrepreneurship courses. This course is given in the form of theory and practice. Results of interview subjects is known that entrepreneurship is a means to foster an entrepreneurial spirit Economics education students. It is also seen from some of the students have been doing entrepreneurial activity